Influence of Gas Flow Rate on Plasma Parameters Produced by a Plasma Jet and its Spectroscopic Diagnosis Using the OES Technique. Issue 1 (November 2020) - Aadim, Kadhim A; Mazhir, Sabah N.; Abdalameer, Nisreen Kh.; Ali, Alyaa H.
Abstract: In this study, the emission spectra of plasma generated from the argon gas in a plasma jet system were measured under normal atmospheric pressure, at constant voltage and for different flow rates from 1–5L/min. The plasma parameters were calculated based on electron density, frequency of plasma, the temperature of an electron, Debye length and the number of particles in the Debye sphere. We employed optical emission spectrometer (OES) technology, which captured the spectrum resulting from the plasma at various flow rates of argon gas. While the flow rate of argon gas to the plasma generated from the discharge current (D.C.) increased, the ranges of the temperature and density of the electron (Te ) were 0.075– 0.1eV and 6.15–9.75x10 17 cm −3, respectively. In contrast, a rise in the intensity of spectral lines was observed.